2012
DOI: 10.1007/s10995-012-1102-z
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Safe Motherhood Services In Diyarbakir: A Community-Based Distribution Project

Abstract: To provide pregnant and puerperal women experiencing problems with receiving health care in Diyarbakir, Turkey, with an education program and counseling to help them attain appropriate health behaviors and to support receiving health care through a community based distribution model. This article is a descriptive report of a qualitative community based distribution project conducted in cooperation with the Women's Research and Implementation Centre (WRIC) of Diyarbakir Metropolitan Municipality (DMM) and Turki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Community-based strategies were reported by Jones and Mondy, [10] Turan and Say, [11] MacArthur et al, [12] Brasington et al, [13] Barnet et al, [14] Coskun and Karakaya [15] and Little et al [16] Although we found this methodology to be the most frequently implemented strategy, some outcomes—such as breastfeeding—showed no evidence of improvement with this approach. [35] However, this observation should not discourage policy makers from using community-based methodologies, as more studies and systematic reviews are necessary to draw firm conclusions about the effectiveness of this strategy.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Community-based strategies were reported by Jones and Mondy, [10] Turan and Say, [11] MacArthur et al, [12] Brasington et al, [13] Barnet et al, [14] Coskun and Karakaya [15] and Little et al [16] Although we found this methodology to be the most frequently implemented strategy, some outcomes—such as breastfeeding—showed no evidence of improvement with this approach. [35] However, this observation should not discourage policy makers from using community-based methodologies, as more studies and systematic reviews are necessary to draw firm conclusions about the effectiveness of this strategy.…”
Section: Discussionmentioning
confidence: 56%
“…Seventeen out of the 23 studies were conducted in high-income countries. [10,12,14,16,17,19,20–25,27–29,31,32] The only 6 studies that were not from high-income countries were carried out on mothers from Brazil [26] (upper-middle income), Turkey [11,15,30] (upper-middle income), Egypt [13] (lower-middle income) and Iran [18] (upper-middle income).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations